Digital Financial Recording and MSME Performance in Rural Areas: The Moderating Effect of Government Support: Pencatatan Keuangan Digital dan Kinerja UMKM di Daerah Pedesaan: Efek Moderasi Dukungan Pemerintah - Yuttama, Faizal Rizky; Widadi, Budi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
Micro, small, and medium enterprises (MSMEs) play a crucial role in sustaining local economies and employment in rural Indonesia. However, many rural MSMEs continue to face financial challenges, such as managing cash flow, maintaining profitability, and ensuring business sustainability, amid increasing digital and market pressures. This study examines how digital financial recording, financial literacy, and human resource capacity affect the financial performance of MSMEs in rural Indonesia, considering government support as a moderating variable. A quantitative explanatory survey design with purposive sampling was used to collect data from 200 MSME owners/managers operating in rural Banyumas Regency. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results reveal that digital financial recording has the strongest positive effect on MSME performance, while financial literacy contributes significantly, albeit to a lesser extent. However, human resource capacity shows no significant direct influence. Notably, government support moderates the relationship between digital financial recording and performance, amplifying the impact of digital adoption on business outcomes. These findings extend the Resource-Based View (RBV) by highlighting the synergy between internal capabilities and external enablers in enhancing MSME competitiveness. The study implies that sustainable MSME growth in rural areas requires digital adoption as well as supportive policies, infrastructure, and training programs. The study provides theoretical and practical insights for MSMEs, policymakers, and financial institutions that aim to accelerate inclusive digital transformation in Indonesia’s rural economy.